The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1985
DOI: 10.1002/chin.198534117
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: REACTIONS OF ARYLIDENECYANOTHIOACETAMIDES WITH CARBONYL COMPOUNDS AND THEIR ENAMINES

Abstract: Umsetzen der Arylidenthioacetamide (I) mit Cyclohexanon und Enamin führt zu den Chinolinthionen (II) (keine Ausb.‐Angabe).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…331 Three-component heterocyclisation of diketone 99, amide 2b and malononitrile in ethanol in the presence of piperidine giving partially hydrogenated pyridinethione 100 provides another example of the synthesis of spiro-fused pyridinechalcogenones. 332 It should be noted that in the last decade, three-component cascade heterocyclisation of amides of cyanoacetic acid or its thio and seleno derivatives with aliphatic, aromatic or heterocyclic aldehydes and 1,3-dicarbonyl compounds in the presence of an excess of an organic base was successfully used in the synthesis of 1H-pyridine-2-chalcogenones, their hydrogenated analogues and salts (see Refs 44 ± 46,199,233,241,243,244,256,257,259,262 ± 268,270,271,274,276,279,284 ± 286,289 ± 291,293,294,302 and 333 ± 339). The synthesis of salts of 4-(aryl,hetaryl)-3-cyano-6-methyl-5-phenylcarbamoyl-1,4-dihydropyridine-2-thiolates 101 from aromatic or heterocyclic aldehydes, amide 2b and acetoacetanilide (85) in the presence of an excess of N-methylmorpholine 257,259,337 provides an example.…”
Section: Cascade Heterocyclisation Involving 13-dicarbonyl Compoundsmentioning
confidence: 99%
“…331 Three-component heterocyclisation of diketone 99, amide 2b and malononitrile in ethanol in the presence of piperidine giving partially hydrogenated pyridinethione 100 provides another example of the synthesis of spiro-fused pyridinechalcogenones. 332 It should be noted that in the last decade, three-component cascade heterocyclisation of amides of cyanoacetic acid or its thio and seleno derivatives with aliphatic, aromatic or heterocyclic aldehydes and 1,3-dicarbonyl compounds in the presence of an excess of an organic base was successfully used in the synthesis of 1H-pyridine-2-chalcogenones, their hydrogenated analogues and salts (see Refs 44 ± 46,199,233,241,243,244,256,257,259,262 ± 268,270,271,274,276,279,284 ± 286,289 ± 291,293,294,302 and 333 ± 339). The synthesis of salts of 4-(aryl,hetaryl)-3-cyano-6-methyl-5-phenylcarbamoyl-1,4-dihydropyridine-2-thiolates 101 from aromatic or heterocyclic aldehydes, amide 2b and acetoacetanilide (85) in the presence of an excess of N-methylmorpholine 257,259,337 provides an example.…”
Section: Cascade Heterocyclisation Involving 13-dicarbonyl Compoundsmentioning
confidence: 99%
“…464,465 Only 3-cyanopyridine-2(1H)-thione 185b and -selenone 185c are obtained on brief refluxing of a mixture of b-enamino ketones 186 or 187 and amide 1b or 1c in ethanol in the presence of acetic acid. 85,347,358,446,463 The stronger the electron-withdrawing properties of the substituent at the sp 2 hybridised carbon atom linked with the amino group, the higher the regioselectivity of the reaction. This is true even for those enamines which have the phenyl and 2-thienyl substituents at the carbonyl group.…”
Section: -Substitutedmentioning
confidence: 99%
“…508 The use of a,b-ynones as substrates in the reactions with cyanoacetamides has been described. 85,347,463,509 3-Cyano-6methyl-4-phenylpyridine-2(1H)-thione (136b) was obtained on stirring a solution of acetylphenylacetylene (251) with cyanothioacetamide (1b) in ethanol in the presence of morpholine at 25 8C. 85,347,463 However, the reaction of equimolar amounts of the ketone 251 with morpholine followed by the addition of the amide 1b to the reaction mixture gave isomeric 3-cyano-4-methyl-6-phenylpyridine-2(1H)-thione 135b.…”
Section: -Substitutedmentioning
confidence: 99%
“…As a rule, the partially hydrogenated pyridine system remains unchanged during the reaction although, in some cases, the formation of oxidation products was noted [4,5]. In a continuation of our investigation, we decided to study the behavior of readily available 5-acetyl-4-aryl-3-cyano-6-methyl-3,4-dihydropyridine-2(1H)-thiones 1a and 1b [7][8][9][10][11] under conditions for cyclocondensation with acetone and malononitrile. We have found that dipyridothiophene derivatives are also formed during this reaction but, in contrast to other tetrahydropyridine derivatives [1-3], cyclocondensation in this case is accompanied by aromatization of the tetrahydropyridine ring.…”
mentioning
confidence: 95%